High-soluble CGA levels are associated with poor survival in bladder cancer. Issue 5 (May 2019) - Szarvas, T; Jardin-Watelet, B; Bourgoin, N; Hoffmann, M J; Nyirády, P; Oláh, C; Széll, T; Csizmarik, A; Hadaschik, B; Reis, H
Abstract : Recently, a neuroendocrine-like molecular subtype has been discovered in muscle-invasive urothelial bladder cancer (BC). Chromogranin A (CGA) is a widely used tissue and serum marker in neuroendocrine tumors. Our aim was to evaluate serum CGA (sCGA) concentrations and their associations with clinical and follow-up data in BC and renal cell carcinoma (RCC). sCGA concentrations were analyzed in the following cohorts: (1) BC training set ( n  = 188), (2) BC validation set ( n  = 125), (3) RCC patients ( n  = 77), (4) healthy controls ( n  = 97). CGA immunohistochemistry and RT-qPCR analyses were performed in 20 selected FFPE and 29 frozen BC tissue samples. Acquired data were correlated with clinicopathological parameters including comorbidities with known effect on sCGA as well as with patients' follow-up data. sCGA levels were significantly higher in BC but not in RCC patients compared to healthy controls. High sCGA levels were independently associated with poor overall and disease-specific survival both in the BC training ( P  < 0.001, P  = 0.002) and validation set ( P  = 0.009, P  = 0.017). sCGA levels were inversely correlated with glomerulus filtrating rate (GFR) and linearly correlated with creatinine clearance and urea concentrations. These correlations were not related to the prognostic value of sCGA. Tissue CGA levels were low to absent independently of sCGA concentrations. Our results demonstrate elevated levels and an independent prognostic value for sCGA in BC but not in RCC. Despite the significant correlation between sCGA and GFR, the prognostic relevance of sCGA seems not related to impaired renal function or other comorbidities.